The rise of the ruling reptiles and ecosystem recovery from the Permo-Triassic mass extinction - Ezcurra, Martín D; Butler, Richard J (Proceedings of the Royal Society. B, Biological sciences, 2018)
One of the key faunal transitions in Earth history occurred after the Permo-Triassic mass extinction ( 252.2 Ma), when the previously obscure archosauromorphs (which include crocodylians, dinosaurs and birds) become the dominant terrestrial vertebrates. Here, we place all known middle Permian-early Late Triassic archosauromorph species into an explicit phylogenetic context, and quantify biodiversity change through this interval. Our results indicate the following sequence of diversification: a morphologically conservative and globally distributed post-extinction 'disaster fauna'; a major but cryptic and poorly sampled phylogenetic diversification with significantly elevated evolutionary rates; and a marked increase in species counts, abundance, and disparity contemporaneous with global ecosystem stabilization some 5 million years after the extinction. This multiphase event transformed global ecosystems, with far-reaching consequences for Mesozoic and modern faunas.